The Routledge companion to race in early modern artistic, material, and visual production
1 online resource
Keywords: "This companion analyzes, frames, and provokes race in insightful ways that center non-white communities' artistic and visual expression in the early modern period, rather than presenting the bias of European artistic and visual depictions of the colonization, enslavement, and subordination of People of Color. The organization of the book moves chronologically, taking a conceptual and thematic framework. This collection will provide a spectrum of object-based case studies of artistic production-objects and object-types-from six continents between the 1400s to 1800s. Contributions take an art historical approach characterized by close analysis of form, function, and meaning, with a particular focus on questions of cross-cultural dialog and provenance. Additionally, there is an emphasis on material culture. The book will be of interest to scholars working in African diaspora studies, art history, visual culture, material culture, Indigenous studies, Renaissance studies, early modern studies, and race and racism studies"--